Environmental, Social and Governance (ESG) Practices and Performance in Shariah Firms: Agency or Stakeholder Theory? - Lee Siew Peng; Mansor Isa (Asian Academy of Management Journal of Accounting and Finance, 2020)
This study examines the impact of ESG (environmental, social and governance) practices on financial performance for a sample of MSCI World Islamic Index firms over the period 2010–2017. We also test whether ESG engagement should be considered an agency or stakeholder issue. Our sample consists of 461 Shariah-compliant firms from 20 countries that are included in the MSCI World Islamic Index. Firms’ involvement in ESG activities is taken from the Thomson Reuters ASSET4 database. The results reveal that ESG aggregate and its individual dimensions are positively related to firm performance, which is consistent with the stakeholder theory. We do not find evidence that ESG is associated with agency problems. The findings suggest that combined ESG and Shariah screenings can increase firm value, enhance more ethical, responsible and transparent practices and thus, create new markets for potential investors.